THE RELATIONSHIP BETWEEN MAN AND HYDROGYMNASTICS ELDERLY: AN INVESTIGATION ON THE GROUNDS THAT AFFECT YOUR PARTICIPATION IN THIS ACTIVITY (Fiep Bulletin - online, 2011)
Among the many reasons to research aimed to increase the number of elderly in society, are the benefits of physical exercises as an important resource to minimize the degenerative effects caused by the aging process. Among the various options for physical exercises, there are those practiced in the water, especially water aerobics, an activity which has been the most recommended by the medical field today. Searching for reasons why older men prefer to adopt a presumed non-participation of this activity, since the generational condition equals with women, it is known that different social trajectories imposed by society, they turn overcoming the biological differences of each sex to justify the current frame. Moreover, with the decline of strength and power, man is more fragile compared to women to fit this new moment of his life: aging. For this research involved 25 men over 60 years, practitioners of frequent water aerobics twice a week. We used questionnaires and interviews that were considered, social, cultural, civil status and professional activity. Making a relationship between empirical / theoretical, we can conclude that the lack of information concerning the activity of water aerobics on the part of the local population and the lack of clarification of the medical part, take men to adopt a posture preconception due to the large presence of women practitioners. But all concerned have changed their stance and attitude to practice today and worry about the spread, benefits and need for this activity for the population, since the location chosen for the study, the activity is offered free. Rethinking gender relations and the meaning of masculinity, can bring the old man a better quality of life for aging.
Keywords: water aerobics; masculinity and education